SERUM LEVEL OF P53 ANTIBODY AND TISSUE EXPRESSION OF P53 IN BREAST CANCER - Al-Hassan, Ahmed; Abdul Muhymen, Nidhal; Al-Ghurabi, Batool (Iraqi Journal of Science, 2024)
Mutation of the p53 tumor suppressor gene is common event in breast cancer. This alteration can result in cellular accumulation of p53 and may also found in serum p53-antibodies. The current study was established to investigate the correlation between the appearance of the serum p53-antibodies and tissue expression of p53 protein, as well as to explore the relationship between serum p53-antibodies and clinicopathological features in patients. Serum p53-antibodies levels were investigated in 40 breast cancer patients, 20 adenofibrosis patients control and in 20 healthy controls by ELISA. Immunohistochemical assay for tissue expression of the p53 mutant protein was also undertaken in the sam`e patients with breast cancer. The median serum levels of p53-antibodies in breast cancer patients was significantly higher than those in patients control and healthy individuals (P<0.05). Antibody against p53 was detected in the sera of 8 patients (20%) whereas the mutant p53 protein was detected in 16 (40%) of the breast cancer tissue. Moreover significant correlation was found between serum p53-antibody status and tissue expression of the mutant p53 protein (P<0.05). Interestingly, the positive rate of p53-antibodes in breast cancer were related to the absence of steroid hormone receptors (P<0.05), but it was not related to age, tumor stage, histologic grade and the size of tumor (P>0.05). These results indicated that the presence of p53- antibodies is probably triggered by the accumulation of tumor p53 protein, and it could be a useful marker to complement routine prognostic factors in breast cancer patients.